Advances in Manufacturing Systems. - Marcos, M. (Key engineering materials., 2012)
This book describes the most recent Advances in Manufacturing Systems presented at the 4 th Manufacturing Engineering Society International Conference (MESIC2011), which was held during September 2011 in Cadiz, Spain. Flexible, Intelligent and Emergent Manufacturing Systems, Quality, Quality Control and Quality Management, Production Engineering and Planning are, together with others, the topics which can be found herein. The book is therefore essential reading matter for manufacturing engineers working in the fields mentioned. Review from Book News Inc.: The 24 selected and peer-reviewed pape.